2021
DOI: 10.1002/jee.20424
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement in engineering education: A systematic literature review

Abstract: Background: Community engagement has recently become a focus in engineering education. However, systematic reviews that catalog best practices and identify research patterns and gaps remain scarce. Purpose: The purpose of this systematic review is to generate insights and findings by reviewing studies focused on community engagement programs in engineering education from 1980 to 2019. This review offers new findings for practitioners and researchers with a menu of proven ideas and provides directions for commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 137 publications
0
29
0
1
Order By: Relevance
“…Previous research [57] systematically reviewed literature on community engagement in undergraduate engineering education between 1980 and 2019. The study identified a need for additional research focusing on community partners' experience.…”
Section: Evaluation Surveymentioning
confidence: 99%
“…Previous research [57] systematically reviewed literature on community engagement in undergraduate engineering education between 1980 and 2019. The study identified a need for additional research focusing on community partners' experience.…”
Section: Evaluation Surveymentioning
confidence: 99%
“…The qualitative technique was chosen because it allows for detailed descriptions of the meaning of occurrences and makes identifying the kind of evidence influenced by change easier (Aflisia et al, 2019;Atmowardoyo, 2018;Yanti & Syahrani, 2022). A comprehensive review of the literature aids in the evaluation and understanding of theme areas (Lovell, 2018;Natarajarathinam et al, 2021;Ramírez-Montoya et al, 2022;Santos et al, 2019;Torres-Carrión et al, 2018). This study carried out fifteen articles to be analyzed in the theme of local wisdom that integrated to education representative of each keyword.…”
Section: Methodsmentioning
confidence: 99%
“…As found in the answers to the first question, a global understanding of the problem of rural depopulation on the part of the students was noted. They were aware of the different aspects that needed to be considered, in order to address this problem; a fundamental aspect to be able to propose complete responses that cover all aspects and that can be really successful [23].…”
Section: "[] Livestock Farming Is the Sector With The Most Notable Po...mentioning
confidence: 99%
“…And an agricultural engineer designs crops to provide food and infrastructures that develop the rural environment and improve rural living conditions. This perception is also not helped by the high number of concepts that have to be explained on technical university courses [22], generally of a very varied nature that are hardly conducive to focusing this type of activity on a specific social issue [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation